2020
DOI: 10.1111/ics.12638
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of caffeine bioadhesive emulgels for cosmetic applications based on formulation design using QbD tools

Abstract: The aim of the present study was to evaluate the influence of the incorporation of caffeine as a model active ingredient on the quality attributes of a bioadhesive emulgel formulation previously optimized by Quality by Design (QbD) tools. Emulgels are emerging topical drug delivery systems for cosmetic or pharmaceutical uses, which combine the advantages of both emulsions and gels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…de Lafuente et al evaluated the impact of the incorporation of caffeine as a model active ingredient on the quality attributes of a bioadhesive emulgel formulation. 92 There were no significant changes in the critical quality attributes and promising stability was observed for at least one year. Moreover, the product exhibited excellent skin adhesion properties in both in vitro / ex vivo bioadhesion experiments using human skin and better caffeine delivery performance than a commercial compounding cream.…”
Section: Current Applicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…de Lafuente et al evaluated the impact of the incorporation of caffeine as a model active ingredient on the quality attributes of a bioadhesive emulgel formulation. 92 There were no significant changes in the critical quality attributes and promising stability was observed for at least one year. Moreover, the product exhibited excellent skin adhesion properties in both in vitro / ex vivo bioadhesion experiments using human skin and better caffeine delivery performance than a commercial compounding cream.…”
Section: Current Applicationsmentioning
confidence: 90%
“…The exceptional stability and tunable rheology of emulsion gels make them a promising candidate for application in food, 48,87,88 pharmaceuticals, 89,90 and cosmetics. 91,92 Furthermore, they can serve as soft templates for designing advanced materials with unique structural and functional properties. 4,26,75 In this section, the most significant and prospective applications of emulsion gels will be discussed in detail (Fig.…”
Section: Current Applicationsmentioning
confidence: 99%
“…Since curcumin emulgels do not contain surfactant, the presence of carbopol gains importance in terms of increasing the viscosity and modifying the rheological properties. C940 provides a shear-thinning or thixotropic property, which affects the product removal or skin application and resistance to incompatibility such as creaming, flocculation or coalescence [27]. Kim et al, (2003) reported a Herschel-Bulkley type of shearthinning flow property by the use of C934 [24,28].…”
Section: Figure 1 Appearance Of Emulgels After Preparationmentioning
confidence: 99%
“…Sainy J, et al [29], has developed an Aloe verabased emulgel formulation of Desoximetasone (DM) for effective treatment of plaque psoriasis and found to increase in in vitro permeation of drug from Aloe vera emulgel and could be employed for the topical treatment of skin ailments. de Lafuente Y, et al [30], evaluated the influence of the incorporation of caffeine in bioadhesive emulgel formulationand results suggested that the optimized emulgel could be an interesting topical biodhesive delivery system for cosmetic applications. Morsy MA, et al [31], formulated and evaluated the efficacy of topical application of ATR-based nanoemulgel on wound healing.…”
Section: Topical Applicationsmentioning
confidence: 99%